ПРЕДЕЛЬНЫЕ СВОЙСТВА ПОРЯДКОВЫХ СТАТИСТИК (Scientific journal of the Fergana State University, 2023)
The paper studies the question of estimating the concentration function for the sums of minima of positive random variables.